Differential Modulation of Transcription Factors and Cytoskeletal Proteins in Prostate Carcinoma Cells by a Bacterial Lactone. (9th May 2018) - Kumar, Senthil R.; Bryan, Jeffrey N.; Eaton, Amanda M.; Robinson, Katherine L.; Gajagowni, Saivaroon
Abstract : The present study tested the effect of a bacterial lactone N-(3-oxododecanoyl)-homoserine lactone (C12-HSL) on the cytoskeletal and transcriptional genes and proteins in prostate adenocarcinoma (PA) cells (DU145 and LNCaP) and prostate small cell neuroendocrine carcinoma (SCNC) PC3 cells including their cellular viability and apoptosis. Our data indicate that cell migration and colony formation were affected in the presence of C12-HSL. C12-HSL induced apoptosis and altered viability of both PA and SCNC cells in a concentration dependent manner as measured by fluorescence and chemiluminescence assays. Compared to PCa cells, noncancerous prostate epithelial cells (RWPE1) were resistant to modification by C12-HSL. Further, the viability of PC3 cells in 3D matrix was suppressed by C12-HSL treatment as detected using calcein AM fluorescence in situ. C12-HSL treatment induced cytoskeletal associated protein expression of vinculin and RhoC, which may have implications in cancer cell motility, adhesion, and metastasis. IQGAP protein expression was reduced in DU145 and RWPE1 cells in the presence of C12-HSL. C12-HSL decreased STAT3 phosphorylation in DU145 cells but increased STAT1 protein phosphorylation in PC3 and LNCaP cells. Overall, these studies indicate that C12-HSL can trigger changes in transcription factors and cytoskeletal proteins and thereby modulate growth and migration properties of PCa cells.